A sexualidade fiscalizada: histórias orais de estudantes assexuais - Jaroczinski, Erick Pires da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
A presente dissertação trata da sexonormatividade, suas raízes eurocêntricas, seu atual impacto na sociedade brasileira, principalmente em relação às pessoas assexuais e as discriminações que os mesmos sofrem, desde questões mais corriqueiras como a infantilização, exclusão social, fetichização, até problemáticas mais sérias, como a anulação de casamentos, patologização e estupro corretivo e/ou marital. A partir da constatação destas problemáticas, é indicado possibilidades para a legislação, currículo e prática pedagógica em educação sexual.

This dissertation addresses the issue of sexual normativity, its Eurocentric roots, and its current impact on Brazilian society, particularly in relation to asexual people and the discrimination they face. The discrimination ranges from more common issues such as infantilization, social exclusion, and fetishization to more serious problems such as the annulment of marriages, pathologization, and corrective/marital rape. Based on the identification of these issues, the dissertation suggests possibilities for legislation, curriculum, and pedagogical practices in sex education.
The surveilled sexuality: oral histories of asexual students
Keywords: Sexonormatividade; Assexualidade; Educação sexual; História oral; Sexnormativity; Asexuality; Sexual education; Oral history